2020
DOI: 10.22271/chemi.2020.v8.i3p.9361
|View full text |Cite
|
Sign up to set email alerts
|

Correlation analysis on different characters in garden pea (Pisum sativum var hortense L.)

Abstract: A field investigation was carried out at experimental farm of Department of Vegetable Science, College of Horticulture, Mandsaur (MP) to estimate the character association for 17 quantitative traits in 20 diverse genotypes of garden pea during the year 2018-19. The correlation studies revealed that pod yield per hectare exhibited highly significant and positive correlation with pod yield (g/plant), pod yield (q/ha), average pod weight (g), total sugar, T.S.S., number of seeds per pod, protein content, number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…The majority of the correlation coefficients established in this study are essentially consistent with prior findings in pea Tiwari et al; [7] Srivastava et al, [9] Jeberson et al [10] Mishra [11] Parihar et al, [3] Their selection practiced for employing these traits individually or simultaneously would bring improvement in other due to correlated response. Thus, selection will be efficient for these characters.…”
Section: Correlation Coefficientssupporting
confidence: 89%
See 1 more Smart Citation
“…The majority of the correlation coefficients established in this study are essentially consistent with prior findings in pea Tiwari et al; [7] Srivastava et al, [9] Jeberson et al [10] Mishra [11] Parihar et al, [3] Their selection practiced for employing these traits individually or simultaneously would bring improvement in other due to correlated response. Thus, selection will be efficient for these characters.…”
Section: Correlation Coefficientssupporting
confidence: 89%
“…Path analysis revealed that plant height had high positive and direct effect on grain yield/plant. It was found that days to 50% flowering and pod length were directly affected grain yield/plant and had positive significant association [3] In earlier study it was found that the key traits for selection for pea yield improvement namely the number of leaves at the vegetative stage, number of leaves, days to first flowering, plant height (cm) at flowering stage, number of seeds/pod, individual seed weight, individual pod weight, pod coat weight, leaf area and 100-seed weight (g) [4] In some earlier studies it was found Meena et al, [5] Bahadur and Devi [6] Tiwari et al, [7] Asha et al [8] similar traits were identified as the most critical components determining pea seed yield. The high positive connection of seed production with the characteristics has already been documented in peas.…”
Section: Correlation Coefficientsmentioning
confidence: 99%
“…These traits were identified as most important component traits and were linked positively with PYPP implying that pod yield would increase by simultaneous selection for these traits. Earlier reports have also confirmed existence of strong positive correlation of PYPP with PH, NPPN, PL, NSPP and NPP (Kumar et al, 2019), days to first picking and shelling percentage (Rahman et al, 2019), average pod weight (Tiwari et al, 2020).…”
Section: Correlation Coefficientsmentioning
confidence: 61%
“…High LAI values at ambient temperature indicate that young leaves on the shoots are able to absorb large amounts of radiation and high CO2 assimilation rate and translocate to other plant parts in large quantities. High temperatures with an average of 35.3 °C reduced LAI in peas, and LAI value in Arka Chaitra variety peas aged 60 days after sowing was 0.88 (Verma, 2019). Exposure to high temperatures also decreased LAI faster due to the presence of wheat leaf senescence.…”
Section: Resultsmentioning
confidence: 94%